Characteristic Features of Hybrid Bridge Structure Models - Machelski, Czesław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This work discusses the classification of bridge structures and their models. Examples of hybrid models are also indicated in the case of homogeneous and mixed structures. Where hybrid design and model cases are presented, an algorithm for the analysis of contact interactions between subsystems is provided.
Keywords: soil-steel bridge; models of hybrid structures; contact forces; investigation; most gruntowo-stalowy; konstrukcje hybrydowe; modele konstrukcji mostowych